Enteric methane emissions model considering diversity of feed resources and system management (DREEM): Case study of pastoralism in Southern Region of France. Methane prediction in sheep production systems in south of France - Mansard L.; Vigan A.; Meuret M.; Lasseur J.; Benoît M.; Lecomte P.; Maguy E. (The value chains of Mediterranean sheep and goat products. Organisation of the industry, marketing strategies, feeding and production systems, 2016)
Ruminant livestock systems are significant sources of greenhouse gases. Herd mobility is a highly adaptive strategy to increase food availability and to face annual variability of forage resources in harsh conditions. Herd mobility also gives the opportunity for increasing flock size and also the farm productivity. The present study aims to estimate enteric methane (CH4) of French Mediterranean sheep farming systems, especially those utilising diversified pastoral feed resources, using a simulating model (Diversity of feed REsources and Enteric Methane emissions, DREEM). Four chosen case studies were representative of contrasted farming system and herd mobility in the French Mediterranean systems, varying from low (sedentary) to high (permanently transhuming) farming systems. First results indicate that CH4 emissions (kg/year) of farming systems increase together with herd size and mobility. At individual level, enteric CH4 emissions from sedentary system ewes were the highest, mainly due to feed intake and feed characteristics. This methodology requires improvements regarding feeding characterization and a larger farming systems sampling. Finally, these results have to be analyzed at a global level by estimating total GHG emissions of the farm, according to economic and LCA models of farming systems.
Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2015/06/16-18, Montpellier (France)